When patrons are patrons: A social-scientific and realistic reading of the parable of the Feast (Lk 14:16b–23) - Eck, Ernest van (HTS teologiese studies, 2013)
This article presents a social-scientific and realistic interpretation of the parable of the Feast. The characteristics of a pre-industrial city are used to determine the realism of the parable. The social-scientific interpretation of the parable considers meals as ceremonies. The cultural values embedded in meals, namely honour and shame, patronage, reciprocity and purity, receive attention. The social dynamics of invitations in the 1st-century Mediterranean world is used as a lens to understand the invitations as an honour challenge, and the social game of gossip is used to obtain an understanding of the excuses in the parable. The conclusion reached is that the parable turns the world in which it is told upside down. As such, the parable has something to say about the injustices that are a part of the society we live in.